TINJAUAN FASILITAS REKREASI DI OBJEK WISATA TAMAN REKREASI ALAM MAYANG KOTA PEKANBARU - Agestia, Desi; Achnes, Syofia (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
This research aims to discover about review of recreational facilities at the natural theme park attractions Alam Mayang Pekanbaru city. .This research aims to: (1) to know the visitor’s responses regarding the recreational facilities at the natural theme park attractions Alam Mayang Pekanbaru city. (2) to find out what are the constraints of the review of recreational facilities at the natural theme park attractions Alam Mayang Pekanbaru city. Quantitatif method was used in this research to describe the issues. 100 people responden used in this research for the sample. The results of this research indicate that based on the research results obtained on the review of recreational facilities at the natural theme park attractions Alam Mayang Pekanbaru city good enough. This is evidenced by the acquisition of the overall total score of  which is 3.046 points.. Keywords: Review, Recreational facilities, Theme park attractions Alam Mayang .